AGRARIAN LAW: A BRANCH OF LAW THAT IS TRUE TO ITS ORIGIN, AND EVOLVED WITH A CLEAR VIEW OF ITS FUTURE - Fisher González, María Vanessa (2023)
This article attempts to analyze the origins and foundations of Agrarian Law. The evolution of agrarian law is a result of the significant influence of the Italian legislation. This work discusses the key factors developed from the general legal theory that have contributed to the identity of this branch of law, such as the different types of risk inherent to agricultural activity and agriculture’s growing vulnerability to climate change. The role of this branch (agrarian law) as a humanistic legal science is highlighted due to its close connection with the International Human Rights Law of the second and third generation. Finally, the ever-changing world concerning food security and environmental issues create the need to delimit the borders of this object of study